2020
DOI: 10.1016/j.ijnss.2020.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for fatigue in breast cancer patients: An umbrella review of systematic reviews

Abstract: Objective To evaluate evidence from published systematic reviews about the effectiveness of exercise interventions on fatigue management in breast cancer patients. Methods PubMed, Web of Science, the Cochrane Library, the Cumulative Index of Nursing and Allied Health (CINAHL), Embase databases, the China National Knowledge Infrastructure (CNKI), the Wanfang database, the China Biomedical Literature Database (CBM), and the VIP database were searched to identify relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 49 publications
(71 reference statements)
2
24
0
4
Order By: Relevance
“…While various drugs have been investigated, the evidence supports combined therapeutic exercise (TE) and psychological interventions as the best therapeutic option for CRF management [ 5 ], showing both efficacy and safety for reducing fatigue in BC survivors [ 10 ]. Recent systematic reviews [ 10 , 11 , 12 , 13 ] support the benefits of aerobic and resistance exercise in patients with CRF in agreement with the Guidelines for Exercise Testing and Prescription in the cancer population by the American College of Sports Medicine (ACSM) [ 14 , 15 ]. In addition, TE is recommended in several clinical practice guidelines to reduce other adverse effects derived from cancer treatments, such as pain, depression, or bone and body weigh alterations [ 10 ].…”
Section: Introductionmentioning
confidence: 98%
“…While various drugs have been investigated, the evidence supports combined therapeutic exercise (TE) and psychological interventions as the best therapeutic option for CRF management [ 5 ], showing both efficacy and safety for reducing fatigue in BC survivors [ 10 ]. Recent systematic reviews [ 10 , 11 , 12 , 13 ] support the benefits of aerobic and resistance exercise in patients with CRF in agreement with the Guidelines for Exercise Testing and Prescription in the cancer population by the American College of Sports Medicine (ACSM) [ 14 , 15 ]. In addition, TE is recommended in several clinical practice guidelines to reduce other adverse effects derived from cancer treatments, such as pain, depression, or bone and body weigh alterations [ 10 ].…”
Section: Introductionmentioning
confidence: 98%
“…Exercise interventions have been proven to alleviate fatigue while improving physical outcomes during and after breast cancer treatment. In a previous umbrella review of 24 systematic reviews on breast cancer and exercise, 21 studies (87.5%) reported that exercise reduced CRF and that both resistance and aerobic exercise helped to relieve fatigue symptoms in BCS [ 11 ]. Moreover, in a systematic review of randomized controlled trials (RCTs) including 36 studies, combinations of aerobic and resistance exercise showed significant associations with improved quality of life in BCS [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, pouco se sabe sobre a etiologia da fadiga relacionada ao câncer 14 . Uma recente revisão de revisões sistemáticas demonstrou que intervenções com exercícios físicos (aeróbio e força) são capazes de reduzir a percepção de fadiga de mulheres diagnosticadas com câncer de mama 15 .…”
Section: Introductionunclassified